North of Home: Obligations to Families of Undocumented Patients - Fins, Joseph J. (The Hastings Center report, 2019)
Undocumented and undomiciled, Gustavo Jiménez had been in the United States for several years. He knew his leg wasn’t right when it began to swell and redden. After the cellulitis spread to his bloodstream, he was found unconscious on the street and admitted to the intensive care unit. He improved quickly and was soon able to tell a social worker his name and that he had family in Quito. Then his health took a turn for the worse, and he developed multisystem organ failure. His doctors believed his prognosis grave and further care futile. They wanted to invoke a provision under their state’s law that allows, at the discretion of at least two physicians, for the withdrawal of life-sustaining therapy for isolated and decisionally incapacitated patients, but the social worker had ethical concerns about the doctors’ desire to make such a momentous decision without family input. She asked for a “time-out to locate his family,” but one of the doctors asserted, “His family isn’t here, and you’ll never find them. Besides we need the bed. The ER is full of patients we can help.” What is owed a patient and family in such a situation?